2014
DOI: 10.1002/ppsc.201400040
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Metallic Nanoclusters: Electron Dynamics, Structure, and Applications

Abstract: Atomically precise Au nanoclusters (NCs) have emerged as fascinating fluorescent nanomaterials and attracted considerable research interest in both fundamental research and practical applications. Due to enhanced quantum confinement, they possess extraordinary optical, electronic, and magnetic properties and therefore are very promising for a wide range of applications, including biosensing, bioimaging, catalysis, photonics, and molecular electronics. Remarkable progress has been reported for the fundamental u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 256 publications
1
69
0
Order By: Relevance
“…Fluorescent metal NCs have emerged as a new class of fluorophores because of several advantageous features [99-102] such as good fluorescence properties and biocompatibility, excellent photostability, sub-nanometer size, and ease of synthesis. The synthesis, biofunctionalization, and applications of metal NCs have been extensively reviewed elsewhere [17,84,103-107].…”
Section: Noble Metal Nanomaterials-based Fluorescent Nanoprobes Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent metal NCs have emerged as a new class of fluorophores because of several advantageous features [99-102] such as good fluorescence properties and biocompatibility, excellent photostability, sub-nanometer size, and ease of synthesis. The synthesis, biofunctionalization, and applications of metal NCs have been extensively reviewed elsewhere [17,84,103-107].…”
Section: Noble Metal Nanomaterials-based Fluorescent Nanoprobes Fomentioning
confidence: 99%
“…There are many advantages to using fluorescent metal NCs as an imaging agent in cells and in vivo , including their unique functionality, ease in conjugation, biocompatibility, large Stoke shift, long lifetime, as well as their photo- and chemical stability [99-102]. A common strategy for intracellular metal ion imaging is based on the analyte-specific quenching of fluorescence NCs probes.…”
Section: Noble Metal Nanomaterials-based Fluorescent Nanoprobes Fomentioning
confidence: 99%
“…While significant strides towards atomically precise synthesis of metal NPs have been made in recent years, [12][13][14] the catalytic mechanisms operational at NP surfaces are not yet entirely understood. It is commonly accepted that clean/pristine NP surfaces are preferable in well-behaved catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it may be concluded that the PL at 530 nm originates from Ag-P3HT and not from thermal degradation of P3HT or Ag NPs. Some research groups reported silver nanoclusters with diameters smaller than 2 nm are luminescent and their fluorescence maximum resides around 680 nm [16,23,24]. Since it was not observed in the PL spectra, we conclude that the luminescent Ag nanoclusters were not formed.…”
Section: Chemical Binding In Ag-p3ht Characterized By 1 H Nmr Ftir Amentioning
confidence: 82%